Analisis Pengetahuan Pajak Kendaraan Bermotor, Biaya Pajak terhadap Kepuasan Masyarakat kepada Pemerintah Pacitan - Winih Imam Masngudi; Hurian Kamela (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the influence of motor vehicle tax knowledge and perceived tax costs on public satisfaction with the performance of the Pacitan Regency Government. Data were collected through a questionnaire distributed to 63 motorcycle vehicle taxpayers in Pacitan. A quantitative approach was employed, using descriptive statistics and multiple linear regression analysis. The findings show that indicators of tax knowledge, such as understanding tax rates, penalty mechanisms, and payment schedules, scored above 3,5 on a Likert scale, indicating a relatively good level of tax literacy. In contrast, perceptions of tax costs tended to be neutral, while transparency and satisfaction with tax fund utilization scored below 3,5. Most respondents expressed satisfaction with the Samsat services regarding process efficiency and service quality. Regression analysis revealed that tax knowledge had a significant positive effect on public satisfaction, whereas perceived tax cost had a negative but not statistically significant effect. This study recommends enhancing tax education, outreach, and transparency in the use of tax revenues to strengthen public trust.